The Effect of Shuttlecock Throwing Training on the Clear Shot Ability of Badminton Players at the UNP Badminton Academy - Rizky Alvarizi; Eri Barlian; Donie; Eval Edmizal (Jurnal Master Penjas & Olahraga, 2026)
This study aims to determine the effect of shuttlecock throwing exercises on the forehand clear ability of athletes at UNP Badminton Academy. The research used a quantitative approach with a pre-experimental method and a one group pretest-posttest design. The population consisted of 23 athletes, while the sample was 8 male athletes aged 11–14 years selected using purposive sampling. The research instrument was a forehand clear test (high clear test) to measure accuracy and technique. Data were collected through pre-test and post-test procedures and analyzed using the Liliefors normality test and paired sample t-test at a significance level of 0.05. The results showed an increase in the average score from 22.25 (pre-test) to 35.88 (post-test). The t-test result (tcount = 3.871 > ttable = 2.365) indicates a significant effect. It can be concluded that shuttlecock throwing exercises effectively improve forehand clear ability.